3D printing porous medical titanium alloy and preparation process thereof
By 3D printing of porous medical titanium alloy and introducing Ca and P elements by two-step microarc oxidation method, the problem of bioinergicity of titanium alloy is solved and the binding strength of its biological activity and implant is significantly improved.
Patent Information
- Application Number
- CN202411562782.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-18
AI Technical Summary
Titanium and its alloys, as bioinert materials, cannot form chemical bonds with bone tissue, resulting in the risk of loosening of the implant.
Porous medical titanium alloys were prepared through 3D printing technology, and biologically active elements such as Ca and P were introduced on its surface by two-step microarc oxidation to form a porous membrane layer to improve biological activity.
It significantly improves the biological activity of titanium alloy, promotes the growth of bone tissue, enhances the binding strength between implants and bones, and extends the service life of the prosthesis.
Smart Images

Figure CN119465339A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical titanium alloys, and in particular to a 3D printed porous medical titanium alloy and a preparation process thereof. Background Art
[0002] 3D printing technology, also known as additive manufacturing technology, has the advantages of rapid production, low cost, wide material selection, high flexibility and high integration, and is widely used in many fields. In the orthopedic industry, 3D printing technology has been industrialized and can produce highly personalized implants based on the patient's own bone morphology to ensure high compatibility with the patient's lesion site. At present, titanium and its alloys are the most widely used metal materials in the 3D printing orthopedic industry. The three-dimensional porous metal implants formed by them have good bone ingrowth ability, which helps bone cells grow in them. Finally, a strong connection is formed between the implant and the bone, which significantly enhances the bonding strength of the implant and promotes bony healing at the interface between the prosthesis and the bone, thereby extending the service life of the prosthesis.
[0003] Titanium and its alloys have been widely used in the field of biomedical materials due to their low density, low modulus, high strength, excellent biocompatibility and corrosion resistance. They are mainly used in artificial hip joints, knee joints, dental implants and tooth roots. However, as bioinert materials, titanium and its alloys cannot form chemical bonds with bone tissue like bioactive materials, which makes the implants at risk of loosening. In order to enhance the bioactivity of titanium and its alloys, it is very necessary to modify their surface activity.
[0004] Micro-arc oxidation is a surface modification technology developed from anodization. It uses high-voltage discharge to grow an oxide layer on the surface of metals such as titanium in situ, thereby achieving surface modification. The oxide film has a high bonding strength with the substrate and is suitable for surfaces with complex morphologies. In addition, by adding specific substances to the electrolyte, active elements such as calcium and phosphorus can be introduced to further enhance the biological activity of the coating.
[0005] Hydroxyapatite is the main inorganic component of human bone tissue, with a Ca / P ratio of 1.67. A film layer with the same Ca / P ratio of 1.67 can be prepared on the surface of titanium alloy through micro-arc oxidation. The film layer is porous and can promote the growth of osteoblasts when implanted in the human body, inducing the deposition of hydroxyapatite on the surface of the implant, thereby promoting the early bone integration of the implant and bone tissue. The Ca and P content and Ca / P are the key factors affecting the formation of hydroxyapatite induced by implants. How to regulate the content of these elements is crucial.
[0006] In summary, in order to solve the problem of biological inertness of titanium and its alloys, it is of great significance to prepare a 3D printed porous medical titanium alloy. Summary of the invention
[0007] The purpose of the present invention is to provide a 3D printed porous medical titanium alloy and a preparation process thereof to solve the problems raised in the prior art.
[0008] To achieve the above object, the present invention provides the following technical solutions: A preparation process for 3D printing porous medical titanium alloy, comprising the following steps: S1: Pretreatment: cleaning the 3D printed porous titanium alloy sample to obtain a 3D printed porous titanium alloy preform; S2: primary micro-arc oxidation: placing the 3D printed porous titanium alloy preform in an electrolyte, and performing a micro-arc oxidation for 1-3 min at a voltage of 200-400 V to obtain a 3D printed porous titanium alloy preform A; S3: Acid treatment: The 3D printed porous titanium alloy preform A is subjected to a first ultrasonic cleaning, a mixed acid solution treatment, and a second ultrasonic cleaning in sequence to obtain a 3D printed porous titanium alloy preform B; S4: secondary micro-arc oxidation: placing the 3D printed porous titanium alloy preform B in an electrolyte, and performing secondary micro-arc oxidation at 350-650V for 2-60min to obtain a 3D printed porous titanium alloy preform C; S5: Post-processing: cleaning and drying the 3D printed porous titanium alloy preform C to obtain a finished product.
[0009] More optimally, the raw materials of the electrolyte include the following components: 5-50 g / L calcium salt, 5-50 g / L phosphate, 10-30 g / L complexing agent, 10-30 g / L hydroxide, and 10-30 g / L arc starting agent.
[0010] More optimally, the molar ratio of Ca:P in the electrolyte is 0.5-3.0; the mass ratio of the complexing agent to the hydroxide is 0.2-2.0.
[0011] The present invention optimizes the composition and concentration of the electrolyte, limits the concentration ratio, and prepares a porous film layer containing biologically active elements such as Ca and P by a two-step micro-arc oxidation method. This patent first forms a TiO2 film layer on the surface of titanium and its alloys through micro-arc oxidation, and successfully introduces Ca and P elements on the surface of titanium and titanium alloys. Pickling can not only remove excess impurities on the surface of the film layer, but also improve the surface morphology of the film layer, increase surface adhesion, and promote the deposition of Ca and P elements during secondary micro-arc oxidation, increase their content, and promote Ca / P to be close to 1.67. In addition, the Ca and P content in the film layer can be changed by regulating the secondary oxidation voltage and oxidation time, and Ca / P can be regulated in the range of 1.60~3.00, thereby expanding the application range of the film layer, reducing production costs and process requirements, and realizing mass production.
[0012] Preferably, the calcium salt comprises one or more of calcium acetate, calcium carbonate, calcium dihydrogen phosphate, calcium hydroxide, calcium oxide or calcium glycerophosphate; the phosphate comprises one or more of calcium dihydrogen phosphate, calcium hydrogen phosphate, calcium phosphate, calcium pyrophosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate or sodium pyrophosphate; the chelating agent comprises one or more of ethylenediaminetetraacetic acid, sodium nitrilotriacetate or diethylenetriamine pentacarboxylate; the hydroxide comprises one or more of sodium hydroxide, calcium hydroxide and potassium hydroxide; the arc starting agent comprises one or two of sodium silicate and sodium hexametaphosphate.
[0013] In the scheme, the arc starting agent has the function of reducing the voltage required for micro-arc oxidation and improving the morphology and performance of the film layer. More optimally, the other process conditions of the primary micro-arc oxidation and the secondary micro-arc oxidation are: the power supply is a pulse power supply, the electrolyte temperature is controlled at 15-80°C, the pulse width is 10-20, the workpiece is insulated and packaged with polytetrafluoroplastic, and stainless steel is the cathode.
[0014] In the scheme, since the solution temperature will rise during spark discharge, the oxidation device also includes a stirring and cooling device; stirring the electrolyte and the low electrolyte temperature can better cool the oxide / electrolyte surface, so that the film has less porosity and more uniform morphology; another effect of stirring is to inhibit side reactions, especially the precipitation of gas on the two electrodes; after the micro-arc oxidation is completed, Ca, P and Ca / P are measured. This step is used to introduce Ca and P on the surface of the titanium alloy to promote the deposition of Ca and P content in the secondary micro-arc oxidation; the secondary micro-arc oxidation is used to form a micro-arc oxidation film layer, increase Ca and P, and regulate Ca / P; The specific steps of the pretreatment in S1 are more optimized: rinse the 3D printed porous titanium alloy sample under a water pressure of 10MPa~40MPa for 10~30min; place it in a grease cleaner with a concentration of 1~5% for ultrasonic treatment for 10~30min; then place it in purified water for ultrasonic treatment for 10~120min, wash three times; dry it at 50~100℃ for 10~60min to obtain a 3D printed porous titanium alloy preform.
[0015] The specific steps of the acid treatment in S3 are as follows: placing the 3D printed porous titanium alloy preform A in a cleaning tank for a first ultrasonic cleaning for 10 to 30 minutes, and drying; transferring to a mixed acid solution, and acid-treating at 20°C for 10 to 60 seconds; transferring to a cleaning tank for a second ultrasonic cleaning for 60 to 120 minutes, and drying; and obtaining a 3D printed porous titanium alloy preform B; Among them, the raw materials of the mixed acid solution include 40% hydrofluoric acid and 38% hydrochloric acid.
[0016] In the scheme, acid treatment is used to remove surface impurities and improve the surface morphology of the micro-arc oxidation film, increase the adhesion of the surface film, facilitate the deposition of Ca and P elements in the secondary micro-arc oxidation, and increase the content of Ca and P elements in the film.
[0017] A more optimized further scheme of the post-processing is: washing the 3D printed porous titanium alloy preform C; transferring it to a silk fibroin solution, letting it stand for 5 to 10 minutes, and taking it out; irradiating it under an ultraviolet lamp for 8 to 15 minutes; washing and drying it to obtain a finished product; The raw materials of the silk fibroin solution include the following components: 15-20 g / L silk fibroin sponge, 0.04-0.06 g / L riboflavin, 0.4-1 g / L additives, and the rest is purified water.
[0018] The preparation method of the additive is more optimized as follows: (1) adding zinc acetate and nano-hydroxyapatite to deionized water and mixing them evenly to obtain a mixed solution A; adding 2-aminobenzimidazole and 2-methylimidazole to deionized water, mixing them evenly, adding the mixed solution A dropwise, centrifuging, washing, and drying to obtain modified ZIF-8; (2) adding polycarboxylated polyethylene glycol to deionized water, mixing them evenly, adding N-hydroxysuccinimide, modified ZIF-8, and polyethyleneimine, adjusting the pH to 5-6, reacting at room temperature for 18-22 hours, dialyzing with deionized water, freezing, and drying to obtain the additive.
[0019] In the scheme, the raw materials for modifying ZIF-8 include the following components: by weight, 0.2-0.3 parts of zinc acetate, 0.05-0.15 parts of nano-hydroxyapatite lime, 0.1-0.2 parts of 2-aminobenzimidazole, 2-3 parts of 2-methylimidazole, and 10-20 parts of deionized water; The raw materials of the additive include the following components: 0.1-0.3 parts of polycarboxylated polyethylene glycol, 0.02-0.04 parts of N-hydroxysuccinimide, 1-2 parts of modified ZIF-8, and 0.1-0.2 parts of polyethyleneimine.
[0020] Compared with the prior art, the present invention has the following beneficial effects: The micro-arc oxidation electrolyte of the present invention has low solution cost, is easy to control, does not contain decomposition components, has stable process, low cost, is suitable for 3D printed titanium alloy implants of various complex shapes, and has good reliability and repeatability in the preparation process.
[0021] The electrolyte composition and concentration were optimized, and active elements such as Ca and P were successfully introduced into the micro-arc oxidation film by controlling the electrolyte composition ratio. A porous coating with uniform thickness and excellent biological activity was successfully prepared by a two-step micro-arc oxidation method, which helps promote the growth of bone tissue after implantation into the human body. By adjusting the oxidation voltage and oxidation time, the Ca / P in the film layer can be effectively regulated from 1.6 to 3.0 without changing the electrolyte, which broadens the applicability of the process conditions, reduces production costs and process requirements, and the raw materials of the invention are easy to obtain, which is convenient for large-scale production.
[0022] In the scheme, a pickling step is added to improve the surface morphology and adhesion of the film layer. At the same time, the micro-arc oxidation step introduces Ca and P elements on the surface of the titanium alloy, which can promote the deposition of Ca and P elements during secondary micro-arc oxidation and significantly increase the Ca and P content.
[0023] In a further scheme, in order to improve the integration of titanium alloy and surrounding bone tissue; riboflavin is used as a photoinitiator, and the silk protein sponge is infiltrated into the pores in the solution, and filled into the porous titanium alloy pores after UV curing, and degraded in the human body after a period of time, so that the titanium alloy surface has good cell compatibility and osteogenic effect; titanium alloy needs to be implanted into the human body through surgery, and bacterial infection in the process will cause inflammatory diseases, and bacterial biofilm will be generated on the surface of titanium alloy, which will certainly cause loosening between titanium alloy and bone; therefore, additives are added to the scheme, and the additives are obtained by reacting the carboxyl groups on polycarboxylated polyethylene glycol with the amino groups on modified ZIF-8 and polyethyleneimine. ZIF-8 can provide zinc ions. The presence of zinc is not only conducive to the proliferation of osteoblasts, but also can inhibit the proliferation of osteoclasts and the adhesion of bacteria. It can synergize with polyethylene glycol and polyethyleneimine to inhibit the growth and reproduction of bacteria.
[0024] Among them, bacteria have strong adhesion on hydrophobic surfaces, but the adhesion will be greatly weakened on hydrophilic surfaces. Polyethylene glycol has strong hydrophilicity; therefore, the hydrophilicity of the titanium alloy surface is improved, making it easier for proteins to adsorb, more conducive to cell adhesion, and more conducive to bone integration. Polyethyleneimine is a cationic polymer. The surface of bacteria is negatively charged, and the surface of positively charged substances is anchored on the alloy surface, so there is less loss in the antibacterial process, so it is more sustainable.
[0025] Modified ZIF-8 is a composite of nano-hydroxyapatite, zinc ions and imidazole, which plays a certain sustained-release role; among them, nano-hydroxyapatite has stable performance under physiological conditions, can provide good support for the adhesion and growth of bone cells, promote the calcification process of bone cells, and play a role in bone conduction. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1This is the surface morphology of the secondary micro-arc oxidation film; Figure 2 The relationship between Ca, P content and Ca / P and oxidation voltage in Examples 6 to 9; Figure 3 Graph showing the relationship between Ca and P content and Ca / P and oxidation time in Examples 10 to 12. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the following specific implementation methods, parts are by mass. In this embodiment, it should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions. Examples include: polyethylene glycol with a molecular weight of 20,000, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; trimellitic anhydride with a CAS number of 552-30-7, purchased from Hubei Shishun Biotechnology Co., Ltd.; zinc acetate with a CAS number of 557-34-6, purchased from Haiyuanye Biotechnology Co., Ltd.; nano-hydroxyapatite lime with a model of JD170601173115, purchased from Shanghai Jiader Chemical Technology Co., Ltd.; 2-aminobenzimidazole with a CAS number of 934-32-7, 2-methylimidazole with a CAS number of 693-98-1, and N-hydroxysuccinimide with a product number of S20179, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; polyethyleneimine with a product number of 181978, purchased from Sigma, USA; and silk fibroin sponge purchased from Suzhou Smet.
[0029] Preparation of polycarboxylated polyethylene glycol: Polyethylene glycol (molecular weight 20,000) was heated at 120°C, trimellitic anhydride was added under nitrogen atmosphere, and mechanical stirring was performed for 8 hours to obtain polycarboxylated polyethylene glycol; wherein the molar ratio of polyethylene glycol to trimellitic anhydride was 1:2.
[0030] The preparation method of the additive is as follows: (1) adding 0.25 parts of zinc acetate and 0.1 parts of nano-hydroxyapatite to 5 parts of deionized water and mixing them uniformly to obtain a mixed solution A; adding 0.1 parts of 2-aminobenzimidazole and 3 parts of 2-methylimidazole to 10 parts of deionized water, mixing them uniformly, adding the mixed solution A dropwise, centrifuging, washing, and drying to obtain modified ZIF-8; (2) adding 0.1 parts of polycarboxylated polyethylene glycol to deionized water, mixing them uniformly, adding 0.02 parts of N-hydroxysuccinimide, 1.5 parts of modified ZIF-8, and 0.15 parts of polyethyleneimine, adjusting the pH to 6, reacting at room temperature for 18 hours, dialyzing with deionized water, and freeze-drying to obtain the additive.
[0031] Example 1: A preparation process for 3D printing porous medical titanium alloy; S1: Pretreatment: The 3D printed porous titanium alloy sample with a size of φ10×10 mm was rinsed under a water pressure of 10 MPa for 30 min, placed in a 1% grease cleaner for ultrasonic treatment for 15 min, then placed in deionized water for ultrasonic treatment for 30 min, replaced with ultrapure water and ultrasonicated for 3 times, and dried at 50°C for 30 min to obtain a 3D printed porous titanium alloy preform; S2: primary micro-arc oxidation: placing the 3D printed porous titanium alloy preform in an electrolyte at 25°C, and performing a micro-arc oxidation for 1 min at a voltage of 400 V and a pulse width of 10 to obtain a 3D printed porous titanium alloy preform A; S3: Acid treatment: The 3D printed porous titanium alloy preform A was placed in a cleaning tank for 15 minutes, dried in a 50°C oven for 20 minutes, cooled to room temperature, and the Ca and P contents therein were detected (see Table 1). Then, it was placed in a mixed acid solution containing 40% hydrofluoric acid and 38% hydrochloric acid, and treated at 20°C for 20 seconds to remove the brown-gray film layer on the surface. After the acid treatment, it was placed in a cleaning tank for 90 minutes, dried in a 65°C oven for 20 minutes, and cooled to room temperature to obtain a 3D printed porous titanium alloy preform B; S4: secondary micro-arc oxidation: placing the 3D printed porous titanium alloy preform B in an electrolyte at 35°C, and performing secondary micro-arc oxidation for 3 min at 400 V and a pulse width of 10 to obtain a 3D printed porous titanium alloy preform C; The contents of the components of the electrolyte are: calcium hydroxide 40g / L, sodium phosphate 30g / L, disodium ethylenediaminetetraacetate 20g / L, sodium hexametaphosphate 18g / L; S5: Post-processing: The 3D printed porous titanium alloy preform C was placed in a cleaning tank for ultrasonic cleaning for 20 min, dried in an oven at 75 °C for 20 min, and the Ca and P contents were detected by SEM and EDS (see Table 2) to obtain the finished product.
[0032] Example 2: A preparation process for 3D printing porous medical titanium alloy; S1: Pretreatment: The 3D printed porous titanium alloy sample with a size of φ10×20×30 mm was rinsed under a water pressure of 15 MPa for 25 min, placed in a 1.5% grease cleaner for ultrasonic treatment for 20 min, then placed in deionized water for ultrasonic treatment for 25 min, replaced with ultrapure water and ultrasonicated for 3 times, and dried at 80°C for 15 min to obtain a 3D printed porous titanium alloy preform; S2: primary micro-arc oxidation: placing the 3D printed porous titanium alloy preform in an electrolyte at 25°C, and performing a primary micro-arc oxidation for 3 min at a voltage of 380 V and a pulse width of 10 to obtain a 3D printed porous titanium alloy preform A; S3: Acid treatment: The 3D printed porous titanium alloy preform A was placed in a cleaning tank for cleaning for 20 minutes, dried in a 70°C oven for 20 minutes, cooled to room temperature, and the Ca and P contents therein were detected (see Table 1). Then, it was placed in a mixed acid solution containing 40% hydrofluoric acid and 38% hydrochloric acid and treated at 20°C for 35 seconds to remove the brown-gray film layer on the surface. After the acid treatment, it was placed in a cleaning tank for cleaning for 120 minutes, dried in a 75°C oven for 25 minutes, and cooled to room temperature to obtain a 3D printed porous titanium alloy preform B; S4: secondary micro-arc oxidation: placing the 3D printed porous titanium alloy preform B in an electrolyte at 45°C, and performing secondary micro-arc oxidation for 8 min at 450 V and a pulse width of 10 to obtain a 3D printed porous titanium alloy preform C; The contents of the components of the electrolyte are: calcium carbonate 15g / L, sodium dihydrogen phosphate 20g / L, sodium nitrilotriacetate 15g / L, sodium hydroxide 15g / L, sodium silicate 10g / L; S5: Post-processing: The 3D printed porous titanium alloy preform C was placed in a cleaning tank for ultrasonic cleaning for 50 min, dried in an oven at 55 °C for 30 min, and the Ca and P contents were detected by SEM and EDS (see Table 2) to obtain the finished product.
[0033] Example 3: A preparation process for 3D printing porous medical titanium alloy; S1: Pretreatment: The 3D printed porous titanium alloy sample with a size of φ30×30×40 mm was rinsed under a water pressure of 20 MPa for 25 min, ultrasonically treated in a 3% grease cleaner for 15 min, ultrasonically treated in deionized water for 20 min, replaced with ultrapure water and ultrasonicated for 3 times, and dried at 90°C for 10 min to obtain a 3D printed porous titanium alloy preform; S2: primary micro-arc oxidation: placing the 3D printed porous titanium alloy preform in an electrolyte at 40°C, and performing a primary micro-arc oxidation for 3 min at a voltage of 400 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform A; S3: Acid treatment: The 3D printed porous titanium alloy preform A was placed in a cleaning tank for cleaning for 30 minutes, dried in a 75°C oven for 20 minutes, cooled to room temperature, and the Ca and P contents therein were detected (see Table 1). Then, it was placed in a mixed acid solution containing 40% hydrofluoric acid and 38% hydrochloric acid and treated at 20°C for 40 seconds to remove the brown-gray film layer on the surface. After the acid treatment, it was placed in a cleaning tank for cleaning for 120 minutes, dried in a 75°C oven for 20 minutes, and cooled to room temperature to obtain a 3D printed porous titanium alloy preform B; S4: secondary micro-arc oxidation: placing the 3D printed porous titanium alloy preform B in an electrolyte at 45°C, and performing secondary micro-arc oxidation for 10 min at 550 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform C; The contents of the components of the electrolyte are: calcium hydroxide 10g / L, calcium phosphate 20g / L, disodium ethylenediaminetetraacetate 20g / L, sodium hydroxide 20g / L, sodium hexametaphosphate 15g / L; S5: Post-processing: The 3D printed porous titanium alloy preform C was placed in a cleaning tank for ultrasonic cleaning for 60 min, dried in an oven at 85 °C for 30 min, and the Ca and P contents were detected by SEM and EDS (see Table 2) to obtain the finished product.
[0034] Example 4: A preparation process for 3D printing porous medical titanium alloy; S1: Pretreatment: The 3D printed porous titanium alloy sample with a size of φ15×15 mm was rinsed under a water pressure of 25 MPa for 15 min, placed in a 4% grease cleaner for ultrasonic treatment for 20 min, then placed in deionized water for ultrasonic treatment for 60 min, replaced with ultrapure water and ultrasonicated for 3 times, and dried at 95°C for 5 min to obtain a 3D printed porous titanium alloy preform; S2: primary micro-arc oxidation: placing the 3D printed porous titanium alloy preform in an electrolyte at 35°C, and performing a primary micro-arc oxidation for 2 min at a voltage of 350 V and a pulse width of 10 to obtain a 3D printed porous titanium alloy preform A; S3: Acid treatment: The 3D printed porous titanium alloy preform A was placed in a cleaning tank for cleaning for 30 minutes, dried in an oven at 85°C for 20 minutes, cooled to room temperature, and the Ca and P contents therein were detected (see Table 1). Then, it was placed in a mixed acid solution containing 40% hydrofluoric acid and 38% hydrochloric acid, and treated at 20°C for 20 seconds to remove the brown-gray film layer on the surface. After the acid treatment, it was placed in a cleaning tank for cleaning for 90 minutes, dried in an oven at 85°C for 20 minutes, and cooled to room temperature to obtain a 3D printed porous titanium alloy preform B; S4: secondary micro-arc oxidation: placing the 3D printed porous titanium alloy preform B in an electrolyte at 40°C, and performing secondary micro-arc oxidation for 10 min at 500 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform C; The contents of the components of the electrolyte are: 18 g / L calcium glycerophosphate, 22 g / L disodium hydrogen phosphate, 20 g / L diethylenetriamine pentacarboxylate, 20 g / L calcium hydroxide, and 20 g / L sodium hexametaphosphate; S5: Post-processing: The 3D printed porous titanium alloy preform C was placed in a cleaning tank for ultrasonic cleaning for 30 min, dried in an oven at 95 °C for 10 min, and the Ca and P contents were detected by SEM and EDS (see Table 2) to obtain the finished product.
[0035] Example 5: A preparation process for 3D printing porous medical titanium alloy; S1: Pretreatment: The 3D printed porous titanium alloy sample with a size of φ50×50 mm was rinsed under a water pressure of 30 MPa for 10 min, placed in a 5% grease cleaner for ultrasonic treatment for 30 min, then placed in deionized water for ultrasonic treatment for 80 min, replaced with ultrapure water and ultrasonicated for 3 times, and dried at 95°C for 5 min to obtain a 3D printed porous titanium alloy preform; S2: primary micro-arc oxidation: placing the 3D printed porous titanium alloy preform in an electrolyte at 45°C, and performing a primary micro-arc oxidation for 2 min at a voltage of 350 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform A; S3: Acid treatment: The 3D printed porous titanium alloy preform A was placed in a cleaning tank for cleaning for 30 minutes, dried in an oven at 85°C for 20 minutes, cooled to room temperature, and the Ca and P contents therein were detected (see Table 1). Then, it was placed in a mixed acid solution containing 40% hydrofluoric acid and 38% hydrochloric acid and treated at 20°C for 35 seconds to remove the brown-gray film layer on the surface. After the acid treatment, it was placed in a cleaning tank for cleaning for 120 minutes, dried in an oven at 95°C for 10 minutes, and cooled to room temperature to obtain a 3D printed porous titanium alloy preform B; S4: secondary micro-arc oxidation: placing the 3D printed porous titanium alloy preform B in an electrolyte at 45°C, and performing secondary micro-arc oxidation for 15 min at 600 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform C; The contents of the components of the electrolyte are: calcium oxide 20g / L, sodium pyrophosphate 35g / L, sodium nitrilotriacetate 30g / L, calcium hydroxide 30g / L, sodium hexametaphosphate 20g / L; S5: Post-processing: The 3D printed porous titanium alloy preform C was placed in a cleaning tank for ultrasonic cleaning for 35 min, dried in an oven at 95 °C for 5 min, and the Ca and P contents were detected by SEM and EDS (see Table 2) to obtain the finished product.
[0036] Example 6: A preparation process for 3D printing porous medical titanium alloy; S1: Pretreatment: The 3D printed porous titanium alloy sample with a size of φ50×50 mm was rinsed under a water pressure of 30 MPa for 20 min, ultrasonically treated in a 5% grease cleaner for 30 min, then ultrasonically treated in deionized water for 120 min, replaced with ultrapure water and ultrasonicated for 3 times, and dried at 80°C for 30 min to obtain a 3D printed porous titanium alloy preform; S2: primary micro-arc oxidation: placing the 3D printed porous titanium alloy preform in an electrolyte at 35°C, and performing a primary micro-arc oxidation for 2 min at a voltage of 400 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform A; S3: Acid treatment: The 3D printed porous titanium alloy preform A was placed in a cleaning tank for cleaning for 30 minutes, dried in an oven at 80°C for 30 minutes, cooled to room temperature, and the Ca and P contents therein were detected (see Table 1). Then, it was placed in a mixed acid solution containing 40% hydrofluoric acid and 38% hydrochloric acid and treated at 20°C for 60 seconds to remove the brown-gray film layer on the surface. After the acid treatment, it was placed in a cleaning tank for cleaning for 90 minutes, dried in an oven at 80°C for 30 minutes, and cooled to room temperature to obtain a 3D printed porous titanium alloy preform B; S4: secondary micro-arc oxidation: placing the 3D printed porous titanium alloy preform B in an electrolyte at 60°C, and performing secondary micro-arc oxidation for 20 min at 500 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform C; The contents of the components of the electrolyte are: calcium hydroxide 40g / L, sodium phosphate 30g / L, disodium ethylenediaminetetraacetate 20g / L, sodium hexametaphosphate 18g / L; S5: Post-processing: The 3D printed porous titanium alloy preform C was placed in a cleaning tank for ultrasonic cleaning for 35 min, dried in an oven at 80 °C for 30 min, and the Ca and P contents were detected by SEM and EDS (see Table 2) to obtain the finished product.
[0037] Example 7: A preparation process for 3D printing porous medical titanium alloy; S1: Pretreatment: The 3D printed porous titanium alloy sample with a size of φ50×50 mm was rinsed under a water pressure of 30 MPa for 20 min, ultrasonically treated in a 5% grease cleaner for 30 min, then ultrasonically treated in deionized water for 120 min, replaced with ultrapure water and ultrasonicated for 3 times, and dried at 80°C for 30 min to obtain a 3D printed porous titanium alloy preform; S2: primary micro-arc oxidation: placing the 3D printed porous titanium alloy preform in an electrolyte at 55°C, and performing a primary micro-arc oxidation for 3 min at a voltage of 400 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform A; S3: Acid treatment: The 3D printed porous titanium alloy preform A was placed in a cleaning tank for cleaning for 30 minutes, dried in an oven at 80°C for 30 minutes, cooled to room temperature, and the Ca and P contents therein were detected (see Table 1). Then, the preform was placed in a mixed acid solution containing 40% hydrofluoric acid and 38% hydrochloric acid and treated at 20°C for 40 seconds to remove the brown-gray film layer on the surface. After the acid treatment, the preform was placed in a cleaning tank for cleaning for 30 minutes, dried in an oven at 80°C for 30 minutes, and cooled to room temperature to obtain a 3D printed porous titanium alloy preform B. S4: secondary micro-arc oxidation: placing the 3D printed porous titanium alloy preform B in an electrolyte at 60°C, and performing secondary micro-arc oxidation for 20 min at 550 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform C; The contents of the components of the electrolyte are: calcium hydroxide 40g / L, sodium phosphate 30g / L, disodium ethylenediaminetetraacetate 20g / L, sodium hexametaphosphate 18g / L; S5: Post-processing: The 3D printed porous titanium alloy preform C was placed in a cleaning tank for ultrasonic cleaning for 60 min, dried in an oven at 80 °C for 30 min, and the Ca and P contents were detected by SEM and EDS (see Table 2) to obtain the finished product.
[0038] Example 8: A preparation process for 3D printing porous medical titanium alloy; S1: Pretreatment: The 3D printed porous titanium alloy sample with a size of φ50×50 mm was rinsed under a water pressure of 30 MPa for 20 min, ultrasonically treated in a 5% grease cleaner for 30 min, then ultrasonically treated in deionized water for 120 min, replaced with ultrapure water and ultrasonicated for 3 times, and dried at 80°C for 30 min to obtain a 3D printed porous titanium alloy preform; S2: primary micro-arc oxidation: placing the 3D printed porous titanium alloy preform in an electrolyte at 60°C, and performing a primary micro-arc oxidation for 3 min at a voltage of 400 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform A; S3: Acid treatment: The 3D printed porous titanium alloy preform A was placed in a cleaning tank for cleaning for 30 minutes, dried in an oven at 80°C for 30 minutes, cooled to room temperature, and the Ca and P contents therein were detected (see Table 1). Then, it was placed in a mixed acid solution containing 40% hydrofluoric acid and 38% hydrochloric acid and treated at 20°C for 40 seconds to remove the brown-gray film layer on the surface. After the acid treatment was completed, it was placed in a cleaning tank for cleaning for 120 minutes, dried in an oven at 80°C for 30 minutes, and cooled to room temperature to obtain a 3D printed porous titanium alloy preform B; S4: secondary micro-arc oxidation: placing the 3D printed porous titanium alloy preform B in an electrolyte at 60°C, and performing secondary micro-arc oxidation for 20 min at 600 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform C; The contents of the components of the electrolyte are: calcium hydroxide 40g / L, sodium phosphate 30g / L, disodium ethylenediaminetetraacetate 20g / L, sodium hexametaphosphate 18g / L; S5: Post-processing: The 3D printed porous titanium alloy preform C was placed in a cleaning tank for ultrasonic cleaning for 30 min, dried in an oven at 80 °C for 30 min, and the Ca and P contents were detected by SEM and EDS (see Table 2) to obtain the finished product.
[0039] Example 9: A preparation process for 3D printing porous medical titanium alloy; S1: Pretreatment: The 3D printed porous titanium alloy sample with a size of φ50×50 mm was rinsed under a water pressure of 30 MPa for 20 min, ultrasonically treated in a 5% grease cleaner for 30 min, then ultrasonically treated in deionized water for 120 min, replaced with ultrapure water and ultrasonicated for 3 times, and dried at 80°C for 30 min to obtain a 3D printed porous titanium alloy preform; S2: primary micro-arc oxidation: placing the 3D printed porous titanium alloy preform in an electrolyte at 55°C, and performing a primary micro-arc oxidation for 3 min at a voltage of 400 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform A; S3: Acid treatment: The 3D printed porous titanium alloy preform A was placed in a cleaning tank for cleaning for 30 minutes, dried in an oven at 80°C for 30 minutes, cooled to room temperature, and the Ca and P contents therein were detected (see Table 1). Then, the preform was placed in a mixed acid solution containing 40% hydrofluoric acid and 38% hydrochloric acid and treated at 25°C for 40 seconds to remove the brown-gray film layer on the surface. After the acid treatment, the preform was placed in a cleaning tank for cleaning for 30 minutes, dried in an oven at 80°C for 30 minutes, and cooled to room temperature to obtain a 3D printed porous titanium alloy preform B. S4: secondary micro-arc oxidation: placing the 3D printed porous titanium alloy preform B in an electrolyte at 60°C, and performing secondary micro-arc oxidation for 20 min at 650 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform C; The contents of the components of the electrolyte are: calcium hydroxide 40g / L, sodium phosphate 30g / L, disodium ethylenediaminetetraacetate 20g / L, sodium hexametaphosphate 18g / L; S5: Post-processing: The 3D printed porous titanium alloy preform C was placed in a cleaning tank for ultrasonic cleaning for 30 min, dried in an oven at 80 °C for 30 min, and the Ca and P contents were detected by SEM and EDS (see Table 2) to obtain the finished product.
[0040] Example 10: A preparation process for 3D printing porous medical titanium alloy; S1: Pretreatment: The 3D printed porous titanium alloy sample with a size of φ50×50 mm was rinsed under a water pressure of 30 MPa for 20 min, ultrasonically treated in a 5% grease cleaner for 30 min, then ultrasonically treated in deionized water for 120 min, replaced with ultrapure water and ultrasonicated for 3 times, and dried at 80°C for 30 min to obtain a 3D printed porous titanium alloy preform; S2: primary micro-arc oxidation: placing the 3D printed porous titanium alloy preform in an electrolyte at 40°C, and performing a primary micro-arc oxidation for 3 min at a voltage of 400 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform A; S3: Acid treatment: The 3D printed porous titanium alloy preform A was placed in a cleaning tank for cleaning for 30 minutes, dried in an oven at 80°C for 30 minutes, cooled to room temperature, and the Ca and P contents therein were detected (see Table 1). Then, the preform was placed in a mixed acid solution containing 40% hydrofluoric acid and 38% hydrochloric acid and treated at 25°C for 40 seconds to remove the brown-gray film layer on the surface. After the acid treatment, the preform was placed in a cleaning tank for cleaning for 30 minutes, dried in an oven at 80°C for 30 minutes, and cooled to room temperature to obtain a 3D printed porous titanium alloy preform B. S4: secondary micro-arc oxidation: placing the 3D printed porous titanium alloy preform B in an electrolyte at 60°C, and performing secondary micro-arc oxidation for 20 min at 600 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform C; The contents of the components of the electrolyte are: calcium hydroxide 40g / L, sodium phosphate 30g / L, disodium ethylenediaminetetraacetate 20g / L, sodium hexametaphosphate 18g / L; S5: Post-processing: The 3D printed porous titanium alloy preform C was placed in a cleaning tank for ultrasonic cleaning for 30 min, dried in an oven at 80 °C for 30 min, and the Ca and P contents were detected by SEM and EDS (see Table 2) to obtain the finished product.
[0041] Example 11: A preparation process for 3D printing porous medical titanium alloy; S1: Pretreatment: The 3D printed porous titanium alloy sample with a size of φ50×50 mm was rinsed under a water pressure of 30 MPa for 20 min, ultrasonically treated in a 5% grease cleaner for 20 min, then ultrasonically treated in deionized water for 120 min, replaced with ultrapure water and ultrasonicated for 3 times, and dried at 80°C for 30 min to obtain a 3D printed porous titanium alloy preform; S2: primary micro-arc oxidation: placing the 3D printed porous titanium alloy preform in an electrolyte at 55°C, and performing a primary micro-arc oxidation for 3 min at a voltage of 400 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform A; S3: Acid treatment: The 3D printed porous titanium alloy preform A was placed in a cleaning tank for cleaning for 30 minutes, dried in an oven at 80°C for 30 minutes, cooled to room temperature, and the Ca and P contents therein were detected (see Table 1). Then, the preform was placed in a mixed acid solution containing 40% hydrofluoric acid and 38% hydrochloric acid and treated at 25°C for 40 seconds to remove the brown-gray film layer on the surface. After the acid treatment, the preform was placed in a cleaning tank for cleaning for 30 minutes, dried in an oven at 80°C for 30 minutes, and cooled to room temperature to obtain a 3D printed porous titanium alloy preform B. S4: secondary micro-arc oxidation: placing the 3D printed porous titanium alloy preform B in an electrolyte at 60°C, and performing secondary micro-arc oxidation for 30 min at 600 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform C; The contents of the components of the electrolyte are: calcium hydroxide 40g / L, sodium phosphate 30g / L, disodium ethylenediaminetetraacetate 20g / L, sodium hexametaphosphate 18g / L; S5: Post-processing: The 3D printed porous titanium alloy preform C was placed in a cleaning tank for ultrasonic cleaning for 30 min, dried in an oven at 80 °C for 30 min, and the Ca and P contents were detected by SEM and EDS (see Table 2) to obtain the finished product.
[0042] Example 12: A preparation process for 3D printing porous medical titanium alloy; S1: Pretreatment: The 3D printed porous titanium alloy sample with a size of φ50×50 mm was rinsed under a water pressure of 30 MPa for 20 min, ultrasonically treated in a 5% grease cleaner for 30 min, then ultrasonically treated in deionized water for 120 min, replaced with ultrapure water and ultrasonicated for 3 times, and dried at 80°C for 30 min to obtain a 3D printed porous titanium alloy preform; S2: primary micro-arc oxidation: placing the 3D printed porous titanium alloy preform in an electrolyte at 55°C, and performing a primary micro-arc oxidation for 3 min at a voltage of 400 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform A; S3: Acid treatment: The 3D printed porous titanium alloy preform A was placed in a cleaning tank for cleaning for 30 minutes, dried in an oven at 80°C for 30 minutes, cooled to room temperature, and the Ca and P contents therein were detected (see Table 1). Then, the preform was placed in a mixed acid solution containing 40% hydrofluoric acid and 38% hydrochloric acid and treated at 25°C for 40 seconds to remove the brown-gray film layer on the surface. After the acid treatment, the preform was placed in a cleaning tank for cleaning for 30 minutes, dried in an oven at 80°C for 30 minutes, and cooled to room temperature to obtain a 3D printed porous titanium alloy preform B. S4: secondary micro-arc oxidation: placing the 3D printed porous titanium alloy preform B in an electrolyte at 55°C, and performing secondary micro-arc oxidation for 40 min at 600 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform C; The contents of the components of the electrolyte are: calcium hydroxide 40g / L, sodium phosphate 30g / L, disodium ethylenediaminetetraacetate 20g / L, sodium hexametaphosphate 18g / L; S5: Post-processing: The 3D printed porous titanium alloy preform C was placed in a cleaning tank for ultrasonic cleaning for 30 min, dried in an oven at 80 °C for 30 min, and the Ca and P contents were detected by SEM and EDS (see Table 2) to obtain the finished product.
[0043] Example 13 is based on Example 9, and the remaining steps are consistent with Example 9; The raw materials of the silk solution include the following components: 12 g / L silk fibroin sponge, 0.05 g / L riboflavin, 0.6 g / L additives, and the rest is purified water; S5: Post-processing: The 3D printed porous titanium alloy preform C was transferred to the silk fibroin solution and allowed to stand for 10 min; taken out and irradiated under a UV lamp (365 nm, 10 W) for 12 min; placed in a cleaning tank for ultrasonic cleaning for 30 min, and dried in an oven at 80 °C for 30 min to obtain the finished product.
[0044] Comparative Example 1 is based on Example 9: no acid treatment is performed after the primary micro-arc oxidation; S1: Pretreatment: The 3D printed porous titanium alloy sample with a size of φ50×50 mm was rinsed under a water pressure of 30 MPa for 20 min, ultrasonically treated in a 5% grease cleaner for 30 min, then ultrasonically treated in deionized water for 120 min, replaced with ultrapure water and ultrasonicated for 3 times, and dried at 80°C for 30 min to obtain a 3D printed porous titanium alloy preform; S2: primary micro-arc oxidation: placing the 3D printed porous titanium alloy preform in an electrolyte at 55°C, and performing a primary micro-arc oxidation for 3 min at a voltage of 400 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform A; S2: Secondary micro-arc oxidation: The 3D printed porous titanium alloy preform A was placed in an electrolyte at 60°C, and subjected to secondary micro-arc oxidation for 20 min at 650 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform C; The contents of the components of the electrolyte are: calcium hydroxide 40g / L, sodium phosphate 30g / L, disodium ethylenediaminetetraacetate 20g / L, sodium hexametaphosphate 18g / L; S3: Post-processing: The 3D printed porous titanium alloy preform C was placed in a cleaning tank for ultrasonic cleaning for 30 min, dried in an oven at 80 °C for 30 min, and the Ca and P contents were detected by SEM and EDS (see Table 2) to obtain the finished product.
[0045] Comparative Example 2 is based on Example 9: Acid treatment is performed before the primary micro-arc oxidation; S1: Pretreatment: The 3D printed porous titanium alloy sample with a size of φ50×50 mm was rinsed under a water pressure of 30 MPa for 20 min, ultrasonically treated in a 5% grease cleaner for 30 min, then ultrasonically treated in deionized water for 120 min, replaced with ultrapure water and ultrasonicated for 3 times, and dried at 80°C for 30 min to obtain a 3D printed porous titanium alloy preform; S2: Acid treatment: The 3D printed porous titanium alloy preform was placed in a cleaning tank for cleaning for 30 minutes, dried in an oven at 80°C for 30 minutes, cooled to room temperature, and the Ca and P contents therein were detected (see Table 1). Then, the preform was placed in a mixed acid solution containing 40% hydrofluoric acid and 38% hydrochloric acid and treated at 25°C for 40 seconds to remove the brown-gray film layer on the surface. After the acid treatment, the preform was placed in a cleaning tank for cleaning for 30 minutes, dried in an oven at 80°C for 30 minutes, and cooled to room temperature to obtain a 3D printed porous titanium alloy preform A. S3: primary micro-arc oxidation: placing the 3D printed porous titanium alloy preform A in an electrolyte at 55°C, and performing a primary micro-arc oxidation for 3 min at a voltage of 400 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform B; S4: secondary micro-arc oxidation: placing the 3D printed porous titanium alloy preform B in an electrolyte at 60°C, and performing secondary micro-arc oxidation for 20 min at 650 V and a pulse width of 20 to obtain a 3D printed porous titanium alloy preform C; The contents of the components of the electrolyte are: calcium hydroxide 40g / L, sodium phosphate 30g / L, disodium ethylenediaminetetraacetate 20g / L, sodium hexametaphosphate 18g / L; S5: Post-processing: The 3D printed porous titanium alloy preform C was placed in a cleaning tank for ultrasonic cleaning for 30 min, dried in an oven at 80 °C for 30 min, and the Ca and P contents were detected by SEM and EDS (see Table 2) to obtain the finished product.
[0046] Comparative Example 3 is based on Example 9: no arc starting agent is added to the electrolyte, and the remaining steps are consistent with Example 9; The contents of each component of the electrolyte are: calcium hydroxide 40g / L, sodium phosphate 30g / L, and disodium ethylenediaminetetraacetate 20g / L.
[0047] Comparative Example 4 is based on Example 13, without adding additives, and the remaining steps are consistent with Example 13; The raw materials of the silk fibroin solution include the following components: 12 g / L silk fibroin sponge, 0.05 g / L riboflavin, and the rest is purified water; S5: Post-processing: The 3D printed porous titanium alloy preform C was transferred to the silk fibroin solution and allowed to stand for 10 min; taken out and irradiated under a UV lamp (365 nm, 10 W) for 12 min; placed in a cleaning tank for ultrasonic cleaning for 30 min, and dried in an oven at 80 °C for 30 min to obtain the finished product.
[0048] Comparative Example 5 is based on Example 13, except that polyethyleneimine and polycarboxylated polyethylene glycol are not added, and the remaining steps are consistent with those of Example 13; The preparation method of modified ZIF-8 is as follows: 0.25 parts of zinc acetate and 0.1 parts of nano-hydroxyapatite are added to 5 parts of deionized water and mixed uniformly to obtain a mixed solution A; 0.1 parts of 2-aminobenzimidazole and 3 parts of 2-methylimidazole are added to 10 parts of deionized water, mixed uniformly, and the mixed solution A is added dropwise, centrifuged, washed, and dried to obtain modified ZIF-8; The raw materials of the silk fibroin solution include the following components: 12 g / L silk fibroin sponge, 0.05 g / L riboflavin, 0.6 g / L modified ZIF-8, and the rest is purified water; S5: Post-processing: The 3D printed porous titanium alloy preform C was transferred to the silk fibroin solution and allowed to stand for 10 min; taken out and irradiated under a UV lamp (365 nm, 10 W) for 12 min; placed in a cleaning tank for ultrasonic cleaning for 30 min, and dried in an oven at 80 °C for 30 min to obtain the finished product.
[0049] Detection test: (1) Detecting the contents of Ca and P after the first micro-arc oxidation and the second micro-arc oxidation in Examples 1 to 12, as shown in Tables 1 and 2; Table 1
[0050] Table 2
[0051] Conclusion: From Figure 2It can be seen that when the electrolyte composition and concentration remain unchanged, the voltage increases, the Ca content gradually increases, the P content slowly decreases, and the Ca / P gradually increases. Therefore, by regulating the voltage, the Ca, P content and Ca / P in the film layer can be effectively adjusted. Figure 3 It can be seen that when the electrolyte composition and concentration remain unchanged, the oxidation time increases, the Ca content first increases and then decreases, the P content has no obvious change, and the Ca / P first increases and then decreases. Therefore, by adjusting the oxidation time, the Ca, P content and Ca / P can be further controlled.
[0052] See Examples 1 to 5 and Figure 1 The present invention provides a new micro-arc oxidation electrolyte, which successfully introduces active elements such as Ca and P into the film layer on the surface of 3D printed titanium alloy by micro-arc oxidation, improves the surface morphology and adhesion by pickling, and deposits Ca and P elements during secondary micro-arc oxidation, significantly increases the Ca and P content, and makes the Ca / P reach 1.6-1.9. The film layer has a porous property, has excellent biological activity, and can promote bone ingrowth. In Table 2, Examples 6 to 12, Figure 2 and Figure 3 The focus was on studying the relationship between the Ca and P content in the film layer and the oxidation voltage and oxidation time. By adjusting the oxidation voltage and oxidation time, the Ca / P ratio can be precisely adjusted from 1.60 to 3.00 without changing the electrolyte. While ensuring biological activity, the limitations of process conditions are broadened. This method not only reduces costs but also simplifies the operating process.
[0053] (2) Cell function assay: Osteoblasts were cultured at a rate of 1×10 4 / cm 2 The density was co-cultured with Example 13 and Comparative Examples 4-5 for 14 days, and the production of osteocalcin was determined by ELSA experiment, as shown in Table 3; Table 3
[0054] Conclusion: Comparative Example 4 is based on Example 13, but no additives are added; resulting in a decrease in the content of osteocalcin; Comparative Example 5 is based on Example 13, but no polyethyleneimine or polycarboxylated polyethylene glycol is added; resulting in a decrease in the content of osteocalcin.
[0055] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A preparation process for 3D printing porous medical titanium alloy, characterized in that: The steps include: S1: Pretreatment: cleaning the 3D printed porous titanium alloy sample to obtain a 3D printed porous titanium alloy preform; S2: primary micro-arc oxidation: placing the 3D printed porous titanium alloy preform in an electrolyte, and performing a micro-arc oxidation for 1-3 min at a voltage of 200-400 V to obtain a 3D printed porous titanium alloy preform A; S3: Acid treatment: The 3D printed porous titanium alloy preform A is subjected to a first ultrasonic cleaning, a mixed acid solution treatment, and a second ultrasonic cleaning in sequence to obtain a 3D printed porous titanium alloy preform B; S4: secondary micro-arc oxidation: placing the 3D printed porous titanium alloy preform B in an electrolyte, and performing secondary micro-arc oxidation at 350-650V for 2-60min to obtain a 3D printed porous titanium alloy preform C; S5: Post-processing: cleaning and drying the 3D printed porous titanium alloy preform C to obtain a finished product.
2. A preparation process for 3D printing porous medical titanium alloy according to claim 1, characterized in that: The raw materials of the electrolyte include the following components: 5-50 g / L calcium salt, 5-50 g / L phosphate, 10-30 g / L complexing agent, 10-30 g / L hydroxide, and 10-30 g / L arc starting agent.
3. A preparation process for 3D printing porous medical titanium alloy according to claim 2, characterized in that: The molar ratio of Ca:P in the electrolyte is 0.5-3.0; the mass ratio of the complexing agent to the hydroxide is 0.2-2.
0.
4. A preparation process for 3D printing porous medical titanium alloy according to claim 2, characterized in that: The calcium salt includes one or more of calcium acetate, calcium carbonate, calcium dihydrogen phosphate, calcium hydroxide, calcium oxide or calcium glycerophosphate; the phosphate includes one or more of calcium dihydrogen phosphate, calcium hydrogen phosphate, calcium phosphate, calcium pyrophosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate or sodium pyrophosphate; the complexing agent includes one or more of ethylenediaminetetraacetic acid, sodium nitrilotriacetate or diethylenetriamine pentacarboxylate; the hydroxide includes one or more of sodium hydroxide, calcium hydroxide and potassium hydroxide; the arc starting agent includes one or two of sodium silicate and sodium hexametaphosphate.
5. The preparation process of a 3D printed porous medical titanium alloy according to claim 1, characterized in that: Other process conditions of the primary micro-arc oxidation and the secondary micro-arc oxidation are: the power supply is a pulse power supply, the electrolyte temperature is controlled at 15-80° C., the pulse width is 10-20, the workpiece is insulated and packaged with polytetrafluoroplastic, and stainless steel is the cathode.
6. The preparation process of a 3D printed porous medical titanium alloy according to claim 1, characterized in that: The specific steps of pretreatment in S1 are: rinse the 3D printed porous titanium alloy sample under a water pressure of 10MPa~40MPa for 10~30min; place it in a grease cleaner with a concentration of 1~5% for ultrasonic treatment for 10~30min; then place it in purified water for ultrasonic treatment for 10~120min, and wash it three times; dry it at 50~100℃ for 10~60min to obtain a 3D printed porous titanium alloy preform.
7. The preparation process of a 3D printed porous medical titanium alloy according to claim 1, characterized in that: The specific steps of acid treatment in S3 are: placing the 3D printed porous titanium alloy preform A in a cleaning tank for a first ultrasonic cleaning for 10 to 30 minutes, and drying; transferring to a mixed acid solution, and acid treatment at 20°C for 10 to 60 seconds; transferring to a cleaning tank for a second ultrasonic cleaning for 60 to 120 minutes, and drying; obtaining a 3D printed porous titanium alloy preform B; Among them, the raw materials of the mixed acid solution include 40% hydrofluoric acid and 38% hydrochloric acid.
8. The process for preparing a 3D printed porous medical titanium alloy according to claim 1, characterized in that: A further scheme of the post-processing is: washing the 3D printed porous titanium alloy preform C; transferring it to a silk fibroin solution, letting it stand for 5 to 10 minutes, taking it out; irradiating it under an ultraviolet lamp for 8 to 15 minutes; washing and drying it to obtain a finished product; The raw materials of the silk fibroin solution include the following components: 15-20 g / L silk fibroin sponge, 0.6-1 g / L riboflavin, 0.4-1 g / L additives, and the rest is purified water.
9. A process for preparing a 3D printed porous medical titanium alloy according to claim 8, characterized in that: The preparation method of the additive is as follows: (1) adding zinc acetate and nano-hydroxyapatite to deionized water and mixing them uniformly to obtain a mixed solution A; adding 2-aminobenzimidazole and 2-methylimidazole to deionized water, mixing them uniformly, adding the mixed solution A dropwise, centrifuging, washing, and drying to obtain modified ZIF-8; (2) adding polycarboxylated polyethylene glycol to deionized water, mixing them uniformly, adding N-hydroxysuccinimide, modified ZIF-8, and polyethyleneimine, adjusting the pH to 5-6, reacting at room temperature for 18-22 hours, dialyzing with deionized water, freezing, and drying to obtain the additive.
10. A finished product obtained according to the preparation process of a 3D printed porous medical titanium alloy according to any one of claims 1 to 9.